LensMouse: augmenting the mouse with an interactive touch display - Yang, Xing-Dong; Mak, Edward; McCallum, David; Irani, Pourang; Cao, Xiang; Izadi, Shahram (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
We introduce LensMouse, a novel device that embeds a touch-screen display – or tangible 'lens' – onto a mouse. Users interact with the display of the mouse using direct touch, whilst also performing regular cursor-based mouse interactions. We demonstrate some of the unique capabilities of such a device, in particular for interacting with auxiliary windows, such as toolbars, palettes, pop-ups and dialog-boxes. By migrating these windows onto LensMouse, challenges such as screen real-estate use and window management can be alleviated. In a controlled experiment, we evaluate the effectiveness of LensMouse in reducing cursor movements for interacting with auxiliary windows. We also consider the concerns involving the view separation that results from introducing such a display-based device. Our results reveal that overall users are more effective with LenseMouse than with auxiliary application windows that are managed either in single or dual-monitor setups. We conclude by presenting other application scenarios that LensMouse could support.
CHI honourable mention award